PENERAPAN METODE BUZZ GROUP TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI MAN KOTO BERAPAK KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Irdasari, Diana - (Pendidikan Biologi, 2014)
Cause of low learning outcomes is influenced by several factors, including lack of teachers using models and a variety of learning methods, so that students are less motivated in the learning process. The low learning achievement of students is the impact of the biological condition of a teacher-centered learning, which is still the dominant source of learning for students. Results biology learning that took place in MAN Koto Berapak still below the minimum completeness criteria (KKM) established school. Minimum completeness criteria in schools is 78. One alternative to improve student learning outcomes is to apply the method of Buzz Group. By applying this method is expected to improve student learning outcomes. This study aims to determine the effect of the application of methods Buzz Group on learning outcomes of students in class XI biology MAN Koto Berapak 2013/2014 school year. This study is a Randomized Experimental Design Control Posttest Only Design. The study population was all students of class XI MAN Koto Berapak enrolled in the second semester of 2013/2014 academic year spread over 3 classes. With purposive sampling technique, then that becomes the study sample class is a class XI student IPA1 as an experimental class of 27 people and the students of class XI IPA3 as the control class of 25 people. The results of the study can be seen that the experimental class had a higher average than the control class where tcount> ttable meaningful research hypothesis is accepted, it can be concluded that the application of the method of Buzz Group influence on student learning outcomes biology class XI Science MAN Koto Berapak District of Bayang Regency Pesisir Selatan.